1996
DOI: 10.1002/jlb.59.2.196
|View full text |Cite
|
Sign up to set email alerts
|

In vitro characterization of rat bone marrow-derived dendritic cells and their precursors

Abstract: Although the rat is commonly used for basic immunology and transplantation research, phenotypic and functional characterization of rat dendritic cells (DCs) lags behind similar studies in the human and mouse. Therefore, these features were examined using DCs propagated from cultures of rat bone marrow maintained in a medium supplemented with granulocyte-monocyte colony-stimulating factor. Analysis of cytospin preparations of cultured cells showd that DCs arise from OX7+ myelomonocytic precursors. Typical matur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
1

Year Published

1997
1997
2007
2007

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 32 publications
2
15
1
Order By: Relevance
“…It has been reported that OX62 represent a unique marker for DC. 38 However, other investigators have reported OX62 is negative on matured rat DCs, 39 and our unpublished data from rat bone marrow culture coincide with their results (data not shown). Therefore, we did not use this to evaluate DC/monocyte type TILs.…”
Section: Gene Therapysupporting
confidence: 84%
“…It has been reported that OX62 represent a unique marker for DC. 38 However, other investigators have reported OX62 is negative on matured rat DCs, 39 and our unpublished data from rat bone marrow culture coincide with their results (data not shown). Therefore, we did not use this to evaluate DC/monocyte type TILs.…”
Section: Gene Therapysupporting
confidence: 84%
“…Our findings differ from those of Spencer and Fabre [21] in that we could not define a second population of APC in the normal rat heart with increased MHC class II expression, but distinct from the population of cells which stain with the ED2 antibody. Furthermore, in contrast to prior morphological observations in normal rat heart [28], we were unable, using immunohistochemistry, to demonstrate a separate dendritic cell population using either OX62 for veiled dendritic cells [29,30] or ED5, a marker of follicular dendritic cells in the lymph node [27]. Negative staining for veiled dendritic cells in normal heart agrees with the findings of Brenan and Puklavec who failed to identify OX62 positive cells in rat heart and skeletal muscle [30].…”
Section: Discussioncontrasting
confidence: 60%
“…An increase of DC in the airways can be the result of an increased influx, a local proliferation, or enhanced survival, or a decreased efflux of DC via the lymph vessels. We found that a 3-d exposure to antigen in sensitized rats induced a 60% increase in the yield of DC grown from bone-marrow precursors in the DC growth factor GM-CSF (52). This is, to our knowledge, the first description of an effect of inflammatory conditions on bone-marrow precursors for DC.…”
Section: Bal T Cells Once These T Cells Have Extravasatedmentioning
confidence: 87%